2022
DOI: 10.1016/j.sjbs.2021.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing of phytomedicine-derived bioactive compounds with promising anti-SARS-CoV-2 potential: Molecular docking, MD simulation and drug-likeness/ADMET studies

Abstract: In view of the potential of traditional plant-based remedies (or phytomedicines) in the management of COVID-19, the present investigation was aimed at finding novel anti-SARS-CoV-2 molecules by in silico screening of bioactive phytochemicals (database) using computational methods and drug repurposing approach. A total of 160 compounds belonging to various phytochemical classes (flavonoids, limonoids, saponins, triterpenoids, steroids etc.) were selected (as initial hits) and screened aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 76 publications
0
22
0
Order By: Relevance
“…AutoDock Vina relies on both empirical and knowledge‐based scoring functions. [ 24 ] PyRx virtual screening tool utilizes AutoDock Vina for molecular docking and was used for the docking study (http://pyrx.sourceforge.net).…”
Section: Methodsmentioning
confidence: 99%
“…AutoDock Vina relies on both empirical and knowledge‐based scoring functions. [ 24 ] PyRx virtual screening tool utilizes AutoDock Vina for molecular docking and was used for the docking study (http://pyrx.sourceforge.net).…”
Section: Methodsmentioning
confidence: 99%
“…Structure-activity relationship exploration of betulinic acid derivatives yielded a strong inhibitor of HCoV-229E replication via the nsp15 endoribonuclease ( Stevaert et al, 2021 ). Betulinic acid was reported to interact strongly with the PLpro from docking and MD simulation studies ( Rudrapal et al, 2022 ), but the inhibition activity and structural modification of betulinic acid against PLpro have not been further studied as far as we know. The affinity and the inhibition activity of betulinic acid ( 1 ) binding to N7-MTase have not been studied as far as we know.…”
Section: Discussionmentioning
confidence: 99%
“…The RdRp has been explored in SARS-CoV-2 for dynamics in the presence of a variety of drug molecules. The studies have found several leads that experience stable conformational dynamics and showed significant intermolecular stability with enzyme's active pockets [98][99][100]. However, RdRp from RVFV is not investigated so far, making the findings of the current study interesting for experimentalists to test them in in vivo and in vitro validation.…”
Section: Root Mean Square Deviation (Rmsd)mentioning
confidence: 91%